The Dynamics of Quraysh Elite Conversion: A Comparative Study of Umar bin Khattab and Khalid bin Walid and Their Impact on Early Islamic Political and Military Structures - Istifarin, Nur Annisa; Ichwayudi, Budi; Majeed, Rehana; Salim, Moh Fuad (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
This research aims to analyze the dynamics of Quraysh elite conversion through a comparative study of Umar bin Khattab and Khalid bin Walid, focusing on their conversion processes, personal transformations, and institutional contributions to the formation of early Islamic power structures. This study employed a qualitative method utilizing the Political Sociology of Religion approach within the framework of Max Weber's thought, particularly focusing on the concepts of legitimation, authority, and the routinization of charisma. The findings revealed that the conversion of Umar bin Khattab and Khalid bin Walid was not merely a matter of individual religious transformation but also constituted an integral part of the political legitimation mechanism in early Islam. Umar's conversion occurred during the early phase of Islam and contributed to strengthening internal legitimacy and to the transformation toward a more rational and institutionalized political-administrative system. Meanwhile, Khalid's conversion occurred during a phase of power consolidation, strengthening the military as an instrument of expansion and stabilization. Comparatively, both figures demonstrate similar patterns of elite conversion in legitimacy transfer, yet differ in their historical contexts and in the forms of institutional contribution. This research concluded that Quraysh elite conversion constituted a crucial mechanism for the legitimation of power, while simultaneously driving the differentiation of political and military functions within the early Islamic state. Thus, this study affirms that the Islamization of elites not only expanded the socio-religious base but also played a significant role in the formation of an organized and expansive power structure.